Blended Learning to Improve the Studentsâ Vocabulary Mastery for Mechanical Engineering Purposes At STT Adisutjipto Yogyakarta - Pertiwi, Dewanti Ratna (Universitas Ahmad Dahlan, 2018)
The study was conducted to improve the low vocabulary mastery of technical terms appeared in English for mechanical engineering purposes at STT Adisutjipto. The students are required to master the technical terms of the three offered concentrations; energy conversion, aircraft maintenance, and manufacture. A blended learning was chosen to improve the studentsâ vocabulary mastery through an action research study. It was divided into two cycles and the data were collected through the journal log, observation sheet, questionnaire, test, and interview. The result indicated that the students enjoyed and improved their vocabulary mastery. The blended learning was seen effectively improving the vocabulary mastery.